IMPORTANT EPISODES FROM THE HISTORY OF DIPLOMATIC RELATIONS OF THE REPUBLIC OF UZBEKISTAN WITH THE COUNTRIES OF THE FAR EAST - Olimova Zahrobegim (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The East Asian region is a very important region in the foreign policy of the Republic of Uzbekistan. Because in this region there are countries such as the People's Republic of China, South Korea and Japan, which are considered important economic partners of Uzbekistan. Since these countries are important economic partners of Uzbekistan today, this article describes the history of the establishment of diplomatic relations between Uzbekistan and these countries.